Cross-syndrome comparison of real-world executive functioning and problem solving using a new problem-solving questionnaire. (December 2016) - Camp, Joanne S.; Karmiloff-Smith, Annette; Thomas, Michael S.C.; Farran, Emily K.
Highlights: Parents/carers rated problem solving for individuals with Williams and Down syndromes. Solution reaching likelihood was lower in Williams syndrome than in Down syndrome. Help seeking was only associated with solution reaching in Down syndrome. Emotional reactions may disrupt problem-solving in Williams syndrome. Real-world executive functioning difficulty levels were high in Williams syndrome. Abstract: Background: Individuals with neurodevelopmental disorders like Williams syndrome and Down syndrome exhibit executive function impairments on experimental tasks (Lanfranchi, Jerman, Dal Pont, Alberti, & Vianello, 2010; Menghini, Addona, Costanzo, & Vicari, 2010), but the way that they use executive functioning for problem solving in everyday life has not hitherto been explored. The study aim is to understand cross-syndrome characteristics of everyday executive functioning and problem solving. Methods: Parents/carers of individuals with Williams syndrome (n = 47) or Down syndrome (n = 31) of a similar chronological age (m = 17 years 4 months and 18 years respectively) as well as those of a group of younger typically developing children (n = 34; m = 8 years 3 months) completed two questionnaires: the Behavior Rating Inventory of Executive Function (BRIEF; Gioia, Isquith, Guy, & Kenworthy, 2000) and a novel Problem-Solving Questionnaire. Results: The rated likelihood of reaching a solution in a problem solving situation was lower for both syndromic groups than the typical group, and lower still for the Williams syndrome group than the Down syndrome group. The proportion of group members meeting the criterion for clinical significance on the BRIEF was also highest for the Williams syndrome group. While changing response, avoiding losing focus and maintaining perseverance were important for problem-solving success in all groups, asking for help and avoiding becoming emotional were also important for the Down syndrome and Williams syndrome groups respectively. Keeping possessions in order was a relative strength amongst BRIEF scales for the Down syndrome group. Conclusion: Results suggest that individuals with Down syndrome tend to use compensatory strategies for problem solving (asking for help and potentially, keeping items well ordered), while for individuals with Williams syndrome, emotional reactions disrupt their problem-solving skills. This paper highlights the importance of identifying syndrome-specific problem-solving strengths and difficulties to improve effective functioning in everyday life.